2020
DOI: 10.3390/agronomy10111659
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Growth of Lettuce and Mizuna under Sole-Source LED Lighting Using Longer Photoperiods with the Same Daily Light Integral

Abstract: Light recommendations for horticultural crops often focus on the optimal daily light integral (DLI) without regard to how that light is delivered throughout each day. Because photosynthesis is more efficient at lower photosynthetic photon flux density (PPFD), we hypothesized that longer photoperiods with lower PPFD results in faster growth than shorter photoperiods with higher PPFD and the same DLI. We quantified the effect of different photoperiods, all providing the same DLI, on photosynthesis and growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 38 publications
7
46
0
Order By: Relevance
“…With increasing PPFD, CCI increased in both species ( Figure 4 A). In previous studies, CCI increased with lower PPFD [ 4 , 18 ]. In those studies, lower PPFDs were combined with longer photoperiods to maintain the same DLI.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…With increasing PPFD, CCI increased in both species ( Figure 4 A). In previous studies, CCI increased with lower PPFD [ 4 , 18 ]. In those studies, lower PPFDs were combined with longer photoperiods to maintain the same DLI.…”
Section: Discussionmentioning
confidence: 83%
“…Mizuna grew faster than lettuce at PPFDs ≥ 125 µmol m −2 s −1 ( Figure 7 A). A previous study conducted to identify the effects of photoperiod on leafy greens found much faster growth of mizuna compared to lettuce [ 18 ]. The difference in biomass between the two crops increased with increasing PPFD (and shorter photoperiods).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, under the same DLI of 8.64 mol m −2 d −1 , the total FW and the total dry weight (DW) of hydroponic lettuce were heavier for the extended light period of 16 h than for the shorter light period of 12 h by 8.6% and 8.5%, respectively [8]. Weaver and van Iersel [9], who tested four different light periods (12,15,18, and 21 h) with the same DLI at 17 mol m −2 d −1 on lettuce grown in a greenhouse, found that the DW of lettuce was positively correlated with the photoperiod, and the highest DW was attained under 21 h. For lettuce and mizuna cultured under the DLI of 16 mol m −2 d −1 provided by white LED in a walk-in growth chamber, the shoot biomass of these crops grown under the photoperiod of 20 h was more than that of 10 h by 16.0% and 18.7%, respectively [10].…”
Section: Introductionmentioning
confidence: 97%